Tuyển tập chuyện cười tiếng Anh - Nguyễn, Hữu Dự (Nxb. Đồng Nai, 2003)
Gồm 50 mẫu chuyện cười: About half of them, He simply bolted, I am wearing my trousers, The three wishes, They won't play the trick on me any more!, We don't want you to get drowned,...